2D and 360° Images: Enhancing Interest and Performance Tasks in Con-temporary Arts - Calvento, Ruth M.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2025)
Contemporary Philippine arts in senior high schools demands innovative approaches to engage students meaningfully. Although virtual reality and 360º videos have been explored in educational settings, limited research has investigated the impact of 360-degree photos, particularly in the context of Philippine Contemporary Arts education. This study addresses this gap by examining the effectiveness of semi-immersive imagery in enhancing student learning. This study aimed to determine the effectiveness of 2D and 360-degree images in improving the learning interest and performance tasks of Grade 12 students in Philippine Contemporary Arts. A quasi-experimental design was employed, involving a control group exposed to traditional 2D images and an experimental group using 360-degree images. Data were collected using pre-tests, post-tests survey which were validated instrument that measured four indicators of learning interest: pleasure, attention, interest, and engagement. Findings revealed that students in the 360-degree group demonstrated significantly higher post-test scores and stronger learning interest across all indicators (p < 0.05) compared to the 2D group. Moreover, their performance tasks showed greater improvement, with mean scores increasing from 13.00 (